From MDT to MTB: the paradigm revolution in pediatric cancer treatment in the era of precision medicine - Haiyan Cheng; Larry L. Wang (Holistic Integrative Oncology)
Abstract Pediatric cancer treatment is undergoing a paradigm shift from multidisciplinary team (MDT) approaches to molecular tumor boards (MTB). This article analyzes the limitations of traditional MDT, the technological reconstruction path of MTB, and the dual challenges of ethics and resource allocation in precision medicine. It reveals the fundamental transformation of the diagnostic and treatment system driven by genomics and proposes integrated strategies for future development.